TANTANGAN PENDIDIK DALAM IMPLEMENTASI KURIKULUM ERA DIGITAL: ANALISIS KOMPETENSI PEDAGOGIS DAN KESIAPAN INFRASTRUKTUR - Aulia Fitri Hanifah; Nur Mahmudi; Imam Junaris (STKIP Subang, 2026)
This study employs a qualitative approach using literature review and descriptive analysis methods to examine the challenges of teachers' pedagogical competencies and digital infrastructure readiness in implementing the curriculum in the digital era. Data were collected from various secondary sources discussing pedagogical aspects, technological readiness, and school infrastructure conditions. The findings indicate that teachers' roles have shifted to facilitators who utilize artificial intelligence and interactive methods to enhance teaching effectiveness. However, significant disparities in the availability of hardware and internet access, especially in remote areas, affect the optimization of digital learning. Additionally, uneven budgets and resource distribution remain major obstacles. The study concludes that successful digital education transformation requires synergy between improving teachers' pedagogical competencies, equitable infrastructure distribution, and collaboration among stakeholders to create a fair and globally competitive learning ecosystem.